Integrated omics approaches provide strategies for rapid erythromycin yield increase in Saccharopolyspora erythraea. Issue 1 (December 2016) - Karničar, Katarina; Drobnak, Igor; Petek, Marko; Magdevska, Vasilka; Horvat, Jaka; Vidmar, Robert; Baebler, Špela; Rotter, Ana; Jamnik, Polona; Fujs, Štefan; Turk, Boris; Fonovič, Marko; et al.
Abstract Background Omics approaches have significantly increased our understanding of biological systems. However, they have had limited success in explaining the dramatically increased productivity of commercially important natural products by industrial high-producing strains, such as the erythromycin-producing actinomyceteSaccharopolyspora erythraea . Further yield increase is of great importance but requires a better understanding of the underlying physiological processes. Results To reveal the mechanisms related to erythromycin yield increase, we have undertaken an integrated study of the genomic, transcriptomic, and proteomic differences between the wild type strain NRRL2338 (WT) and the industrial high-producing strain ABE1441 (HP) ofS. erythraea at multiple time points of a simulated industrial bioprocess. 165 observed mutations lead to differences in gene expression profiles and protein abundance between the two strains, which were most prominent in the initial stages of erythromycin production. Enzymes involved in erythromycin biosynthesis, metabolism of branched chain amino acids and proteolysis were most strongly upregulated in the HP strain. Interestingly, genes related to TCA cycle and DNA-repair were downregulated. Additionally, comprehensive data analysis uncovered significant correlations in expression profiles of the erythromycin-biosynthetic genes, other biosynthetic gene clusters and previously unidentified putative regulatory genes. Based on this information, we demonstrated that overexpression of several genes involved in amino acid metabolism can contribute to increased yield of erythromycin, confirming the validity of our systems biology approach. Conclusions Our comprehensive omics approach, carried out in industrially relevant conditions, enabled the identification of key pathways affecting erythromycin yield and suggests strategies for rapid increase in the production of secondary metabolites in industrial environment.